Dispensing Device of Powder Salt - Won Bang, Gul; Ho Kim, Yong (International Journal of Engineering and Technology, 2018)
Background/Objectives:Spray device that dispenses powder salt throughout the air is able to inhale a fixed quantity of it in the air through respiratory organ. In order to not only sterilize but purify accumulates fine dust in a human lungs, automatic system with convergence of IT technology is developed to be able to dispense powder salt in the air.Methods/Statistical analysis: In order to dispense power salt in the air it is configured as a feeder that provides a fixed quantity from powder salt supply container and dispenser that can spray powder salt. The injector is composed of crusher device to be able to prevent salt from sticking together and discharge device that is releasing powder salt outside by blowing up.Findings: Powder salt dispenser makes salt powder equivalent to fine dust or ultra fine dust to dispense in the air for the purpose of improving immunity level and resistance to germs through sterilizing action in case of induction of inflammation due to harmful substance in blood vessel or skin problem. Injection quantity of powder salt is 2.5g/min and it will be a sufficient quantity to breathe in salt in an enclosed space of 6m*6m during two minutes.Improvements/Applications: This device is design to decrease damage caused by occurrence of fine dust. In order to get rid of inhaled fine dust to human body salt is provided to be able to inhale condition. Particles of salt could not only wash off fine dust that causes various kind of disease but also improve sterilizing action and immunity level. It is available at a hospital or healing center as well. Â